Inorganic dietary nanoparticles in intestinal barrier function of inflammatory bowel disease: allies or adversaries? - Luo, Duo; Luo, Guifang; Xu, Haoming; Li, Kangbao; Li, Zhaotao; Zhang, Cong (Frontiers in Immunology, 2025)
Inorganic dietary nanoparticles (IDNPs) are frequently utilized as food additives and in packaging, resulting in their exposure becoming a substantial yet often overlooked concern for patients with inflammatory bowel disease (IBD). Considering that impaired intestinal barrier function plays a central role in the pathogenesis of IBD, this review concentrates on the roles and mechanisms of IDNPs in the intestinal barrier (physical, chemical, biological, and immune barriers) of IBD patients. Previous studies have shown that different types of nanoparticles have varying effects on animals in diverse states. In this context, factors such as the source, size, shape, dosage, and duration of action of the nanoparticles, as well as the species, gender, dietary habits, and age of the animals, significantly influence research outcomes. Future studies should undertake more comprehensive explorations into the effects and mechanisms of IDNPs with diverse sources and properties in IBD patients.